Analysis of the Need for Number of Nurses Based on Workload at the Inpatient Installation of the Sorong Regency Hospital, West Papua, during the Covid-19 Pandemic - Rudiyanto Mirino; Gustaaf A. E. Ratag; John J. Wantania (Universitas Sam Ratulangi, 2022)
Abstract: Provision of health services is closely related to human resources in achievement of good implementation of services especially during the covid-19 pandemic. The need for health workers in accordance with this pandemic situation is very necessary to provide qualified health services. This study aimed to analyze the need for number of nurses in terms of workload on the inpatient installations of RSUD Dr. Jhon Piet Wanane, Sorong, due to the increasing need for health services during the Covid-19 pandemic. This was a quantitative and descriptive study. Informant selection was based on the knowledge and understanding of the nurses on duty in the inpatient rooms. Calculation of the number of health personnel needs was carried out using a calculation formula which was number of cases handled multiplied by the number of treatment times then divided by the effective working time of nurses in one year. The results showed that the highest workload was in the inpatient class I and II, which was 1,065 minutes (24%), however, it was still below standard level. In conclusion, there is no high workload in RSUD Kabupaten Sorong. Hospital management could use a real formula adapted to workload situation to calculate the need for nurses and review the application model of nursing care management. Keywords: needs of human resources; health services; workloadÂ Abstrak: Pemberian pelayanan kesehatan berkaitan erat dengan penyediaan sumber daya manusia kesehatan (SDMK) agar penyelenggaraan pelayanan kesehatan dapat berjalan dengan baik terlebih pada masa pandemi Covid-19. Kebutuhan tenaga kesehatan yang memadai pada kondisi pandemi saat ini sangat diperlukan untuk memberikan pelayanan kesehatan yang berkualitas. Penelitian ini bertujuan untuk mengetahui kebutuhan jumlah tenaga perawat ditinjau dari beban kerja pada instalasi rawat inap RSUD Dr. Jhon Piet Wanane Kabupaten Sorong akibat meningkatnya kebutuhan akan pelayanan kesehatan pada masa pandemi Covid-19. Jenis penelitian ialah kuantitatif deskriptif. Informan pene-litian dipilih berdasarkan pengetahuan dan pemahaman perawat yang bertugas pada ruang rawat inap. Perhitungan jumlah kebutuhan tenaga kesehatan menggunakan rumus perhitungan banyaknya kasus yang ditangani dikalikan dengan jumlah waktu tindakan kemudian dibagi dengan waktu kerja efektif perawat dalam satu tahun. Hasil penelitian mendapatkan beban kerja tertinggi di ruang rawat inap kelas I, II yaitu 1.065 menit (24%) yang masih di bawah nilai standar. Simpulan penelitian ini ialah tidak ditemukan beban kerja yang tinggi di RSUD Kabupaten Sorong. Manajemen RSUD dapat menggunakan formula riil situasi di lapangan untuk menghitung kebutuhan tenaga perawatan di ruangan dan meninjau kembali model penerapan manajemen asuhan keperawatanKata kunci: kebutuhan sumber daya manusia kesehatan; pelayanan kesehatan; beban kerja